TRACE ELEMENT PARTITIONING BETWEEN MICA- AND AMPHIBOLE-BEARING GARNET LHERZOLITE AND HYDROUS BASANITIC MELT: 1. EXPERIMENTAL RESULTS AND THE INVESTIGATION OF CONTROLS ON PARTITIONING BEHAVIOUR - Adam J.; Green T. (My University, 2006)
Thirty five minor and trace elements (Li, Be, B, Sc, Cu, Zn, Ga, Ge, As, Rb, Nb, Mo, Ag, Cd, In, Sn, Sb, Cs, Ba, La, Ce, Nd, Sm, Tb, Ho, Tm, Lu, Hf, Ta, W, Tl, Pb, Bi, Th and U) in experimentally produced near-liquidus phases, from a primitive nelpheline basanite from Bow Hill in Tasmania (Australia), were analysed by LAM ICP-MS. A number of halogens (F, Cl and I) were also analysed by electron microprobe. The analyses were used to determine mineral/melt partition coefficients for mica, amphibole, garnet, clinopyroxene, orthopyroxene and olivine for conditions close to multiple saturation of the basanite liquidus with garnet lherzolite (approximately 2.6 GPa and 1,200°C with 7.5 wt% of added H2O). A broader range of conditions was also investigated from 1.0 GPa and 1,025°C to 3.5 GPa and 1,190°C with 5-10 wt% of added H2O. The scope and comprehensiveness of the data allow them to be used for two purposes, these include the following: an investigation of some of the controlling influences on partition coefficients; and the compilation of a set partition coefficients that are directly relevant to the formation of the Bow Hill basanite magma by partial melting of mantle peridotite. Considering clinopyroxene, the mineral phase for which the most data were obtained, systematic correlations were found between pressure and temperature, mineral composition, cation radius and valence, and ΔGcoulb (the coulombic potential energy produced by substituting a cation of mismatched valence into a crystallographic site). ΔGcoulb is distinctly different for different crystallographic sites, including the M2 and M1 sites in clinopyroxene. These differences can be modelled as a function of variations in optimum valence (expressed as 1 sigma standard deviations) within individual M1 and M2 site populations. © Springer-Verlag 2006.